t-Darpp stimulates protein kinase A activity by forming a complex with its RI regulatory subunit - Theile, Dirk (Cellular signalling, 2017)
t-Darpp is the truncated form of the dopamine- and cAMP-regulated phosphoprotein of 32kDa (Darpp-32) and has been demonstrated to confer resistance to trastuzumab, a Her2-targeted anticancer agent, via sustained signaling through the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/Akt pathway and activation of protein kinase A (PKA). The mechanism of t-Darpp-mediated PKA activation is poorly understood. In the PKA holoenzyme, when the catalytic subunits are bound to regulatory subunits RI or RII, kinase activity is inhibited. We investigated PKA activity and holoenzyme composition in cell lines overexpressing t-Darpp (SK.tDp) or a T39A phosphorylation mutant (SK.tDpT39A), as well as an empty vector control cell line (SK.empty). We also evaluated protein-protein interactions between t-Darpp and PKA catalytic (PKAc) or regulatory subunits RI and RII in those cell lines. SK.tDp cells had elevated PKA activity and showed diminished association of RI with PKAc, whereas SK.tDpT39A cells did not have these properties. Moreover, wild type t-Darpp associates with RI. Concurrent expression of Darpp-32 reversed t-Darrp's effects on PKA holoenzyme state, consistent with earlier observations that Darpp-32 reverses t-Darpp's activation of PKA. Together, t-Darpp phosphorylation at T39 seems to be crucial for t-Darpp-mediated PKA activation and this activation appears to occur through an association with RI and sequestering of RI away from PKAc. The t-Darpp-RI interaction could be a druggable target to reduce PKA activity in drug-resistant cancer.
Gesehen am 10.04.2018